KELAYAKAN PRODUKTIVITAS BIJI KOPIMELALUI PERANCANGAN SILVIKULTUR SECARA EKOLOGIS STUDI DI AREAL KONSESI HKm KPHL BATUTEGI LAMPUNG - Nurul Dwi P; Samsul Bakri; Susni Herwanti; Agus Setiawan (Jurnal Hutan Tropis, 2019)
Lampung Province with South Sumatra, which has occupied Indonesia as the third largest exporter after Brazila in the past three decades. This export appeal has triggered the encroachment of protected forests for coffee cultivation (Bakri et al, 2018), which is now an eco-labeling issue of the risk of degradation on environmental quality. Since the coffee is already a protected HHBK product especially following HKm scheme, it has been conducted this research from August to September 2017 in Kecamatan Air Naningan, Tanggamus District, Lampung. Observation of tree shade, pole, shrubs and nurseries has made 30 plots of samples of vegetation observations over coffee agroforestry. Productivity data of coffee, kinds and types of inputs and prices in cultivation were obtained through interviews of HKm participants in accordance with each plot plus 2 other participants adjacent to the land. The OLS method is used to formulate the matetamtical relationship between coffee productivity and shading type for tree phase [Y1] and pole phase [Y2] with 5% accuracy level. Selection is done (i) choosing shade type which has positive parameter value to [Y1] only to be used to establish combination of silvicultural improvement design; (ii) perform input-output analysis to assign Net B / C, NPV and IRR for each type and phase shade as a local ecological silviculture act. Conclusion: (1) Types [and phases] that have real positive effects: petai (Parkia speciosa), and medang (Phoebe hunanensis), sonokeling (Dalbergia latifolia) [poles], (2) silviculture improvement plan with coffee composition + petai + medang and coffee + petai + sonokeling have NPV Rp.230.981.284 and Rp. 232.301.462, Net B / C obtained 61,3 and 62,1 and IRR obtained by 33,9% and 34,0%.Lampung Province with South Sumatra, which has occupied Indonesia as the third largest exporter after Brazila in the past three decades. This export appeal has triggered the encroachment of protected forests for coffee cultivation (Bakri et al, 2018), which is now an eco-labeling issue of the risk of degradation on environmental quality. Since the coffee is already a protected HHBK product especially following HKm scheme, it has been conducted this research from August to September 2017 in Kecamatan Air Naningan, Tanggamus District, Lampung. Observation of tree shade, pole, shrubs and nurseries has made 30 plots of samples of vegetation observations over coffee agroforestry. Productivity data of coffee, kinds and types of inputs and prices in cultivation were obtained through interviews of HKm participants in accordance with each plot plus 2 other participants adjacent to the land. The OLS method is used to formulate the matetamtical relationship between coffee productivity and shading type for tree phase [Y1] and pole phase [Y2] with 5% accuracy level. Selection is done (i) choosing shade type which has positive parameter value to [Y1] only to be used to establish combination of silvicultural improvement design; (ii) perform input-output analysis to assign Net B / C, NPV and IRR for each type and phase shade as a local ecological silviculture act. Conclusion: (1) Types [and phases] that have real positive effects: petai (Parkia speciosa), and medang (Phoebe hunanensis), sonokeling (Dalbergia latifolia) [poles], (2) silviculture improvement plan with coffee composition + petai + medang and coffee + petai + sonokeling have NPV Rp.230.981.284 and Rp. 232.301.462, Net B / C obtained 61,3 and 62,1 and IRR obtained by 33,9% and 34,0%.